When the days are(n’t) numbered: Calendar calculations in transparent and opaque systems - Ziyi Zhuang; Norbert Vanek (Language and Cognition)
Calendar calculations, the process of computing the target day or month, exhibit peculiar differences across languages. In systems like English, calendar labels are largely opaque (Tuesday, August), which invites calculations to rely more heavily on verbal listing. In transparent systems, like Chinese, habitual labeling of calendar terms numerically (Tuesday = Day 2, August = Month 8) facilitates fast numerical operations instead of verbal listing. This study examines the effects that different levels of transparency of the calendar naming system may have on calculations in the speakers’ first and second language. Chinese–English bilinguals were tested alongside English and Chinese controls. Forced-choice calendar calculations (day, month, hour and year) and self-reported strategies were used as tasks to tap into participants’ calculation speed, accuracy and temporal reasoning. In the calculation questions, we manipulated Distance (short/long), Direction (forward/backward), Input (linguistic/numerical) and Boundary (within/across). More complex Month calculations significantly differed across groups while easier day calculations did not. The English group reported reliance on verbal listing while the Chinese and the Bilingual groups preferred numerical reasoning. These findings bring new evidence for linguistic relativity in the form of modulations of calendar processing speed changing as a function of linguistic transparency, input type and task demand.